Influence of the cordierite lining on the lost foam casting process - Trumbulović Ljiljana; Gulišija Zvonko; Aćimović-Pavlović Zagorka; Andrić Lj. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper discuss the influence of the refractory cordierite lining on the structure and mechanical properties of Al-Si and Al-Cu casings obtained from the Lost foam casting process. So far there has not been any report of the research on cordierite lining in the literature and moreover the cordierite ceramics have never been used in foundries. In the light of these facts this paper investigates the possibility of using cordierite for manufacturing evaporable model refractory linings. Our results indicate that the application of cordierite ceramics is comparable to talc-based refractory linings in both Al-Cu and Al-Si castings, while cordierites are favorable in Al-Cu case due to their higher melting temperature.